A review of cloud-based bim technology in the construction sector - Wong, J.; Wang, Xiangyu; Li, H.; Chan, G.; Li, H. (International Council for Research and Innovation in Building and Construction, 2014)
Cloud computing technology is regarded as a major transformational force that is causing unprecedented change across the communication and business disciplines. In the architecture, engineering and construction sector, cloud-BIM integration is considered to be the second generation of building information management (BIM) development, and is expected to produce another wave of change across the construction industry. Despite this, few studies to date have attempted to summarise the research literature on cloud-BIM. This paper explores the literature to identify the substantive work on cloud-BIM, particularly regarding building life cycle management, to provide valuable insight for practitioners and to propose avenues for further research. Thirty academic sources, including refereed journal articles and conference papers, were retrieved and analysed in terms of their research focus and nature of application. The review revealed that most cloud-BIM research has focused on the building planning/design and construction stages. The findings suggest that more research should be directed towards operation, maintenance and facility management, energy efficiency and the demolition and deconstruction stages of building life cycle management. Further empirical research on organisational and legal issues, including security, responsibility, liability and model ownership, of the cloud-BIM model is also needed.